2017
DOI: 10.1038/emi.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and role of cave-dwelling hematophagous insects in pathogen transmission in the Afrotropical region

Abstract: The progressive anthropization of caves for food resources or economic purposes increases human exposure to pathogens that naturally infect cave-dwelling animals. The presence of wild or domestic animals in the immediate surroundings of caves also may contribute to increasing the risk of emergence of such pathogens. Some zoonotic pathogens are transmitted through direct contact, but many others require arthropod vectors, such as blood-feeding insects. In Africa, hematophagous insects often play a key role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Although the vectors of the Australian T. noyesi are also unknown, molecular surveys have suggested that tabanid flies and biting midges can be its vectors (Botero et al, 2016). A large diversity of haematophagous hemipterans (triatomines and cimicids) and dipterans (including cave-dwelling sand flies and culicids) including a range of ectoparasites (flies, ticks, mites, cimicids and fleas) feed on bats (Obame-Nkoghe et al, 2017), and all these arthropods should allow for both cyclical and mechanical trypanosome transmission. In addition to abundance of bat species living in diverse environments, gregariousness behaviour of bats favour host switching of ectoparasites.…”
Section: Triatomines and Cimicids Play Important Roles In The Evolutimentioning
confidence: 99%
“…Although the vectors of the Australian T. noyesi are also unknown, molecular surveys have suggested that tabanid flies and biting midges can be its vectors (Botero et al, 2016). A large diversity of haematophagous hemipterans (triatomines and cimicids) and dipterans (including cave-dwelling sand flies and culicids) including a range of ectoparasites (flies, ticks, mites, cimicids and fleas) feed on bats (Obame-Nkoghe et al, 2017), and all these arthropods should allow for both cyclical and mechanical trypanosome transmission. In addition to abundance of bat species living in diverse environments, gregariousness behaviour of bats favour host switching of ectoparasites.…”
Section: Triatomines and Cimicids Play Important Roles In The Evolutimentioning
confidence: 99%
“…Studies on mosquito blood meals have revealed that mosquito could feed on bats and other mammals [ 62 , 63 ]. Bat flies appear to be highly bat-specific, adapted to their lifestyle [ 77 , 78 , 79 , 80 ] and are involved in the transmission of pathogens [ 64 ]. However, this specificity would preclude interspecies pathogen transmission.…”
Section: Vector-borne Route Of Transmissionmentioning
confidence: 99%
“…Underground spaces such as natural caves, mining galleries, tunnels and culverts (henceforth referred to as ‘caves’) are resting and hibernation shelters for numerous families of insects, including hematophagous Diptera such as Psychodidae, Ceratopogonidae and Culicidae (Obame-Nkoghe et al 2017a ; Carvalho et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%